Fixed-Bed Column Studies for the Removal of Congo Red Using Simmondsia chinesis (Jojoba) and Coated with Chitosan - Amina Abdel Meguid Attia; Mona Abdel Hamid Shouman; Soheir Abdel Atty Khedr; Nevin Ahmed Hassan (Indonesian Journal of Chemistry, 2018)
The goal of this article describes the potential of utilizing jojoba leaves and also modified with chitosan as an efficient adsorption materials for Congo red dye removal in a fixed-bed column. Inlet dye concentration, feed flow rate and bed height had a great influence on determining the breakthrough curves. The percentage dye removal was found to be approximately 69% of coated jojoba leaves with flow rate 3 mL/min, initial concentration 50 mg/L and 4 cm bed height. The dye uptake capacity at equilibrium (qe) for coated jojoba leaves showed higher values than that found for jojoba leaves. On this basis, this implies that the amino groups played an important role during the adsorption process. Breakthrough curves were satisfactorily in good agreement with both Thomas and Yoon-Nelson models based on the values of correlation coefficient (R2 ≥ 96).This study serves as a good fundamental aspect of wastewater purification on jojoba leaves as a novel adsorbent for the uptake of Congo red dyes from aqueous solution in a column system.